Underwriter Certification and the Role of New Investors in Seasoned Equity Offerings in Hong Kong - Yang, Lina (2014)
Private equity placement and open offer are two methods of issuing new shares is seasoned equity offering. Even though open offer is believed similar to private equity placement, it was predicted that the announcement effects of this two types of offerings are opposite. This thesis explores the impact of announcement effects of this two types of offerings in Hong Kong during 2010 to 2013. Market model and multiple linear regression analysis are used to figure out the announcement effects of two types of offerings and the factors that influence the announcement effect. It is proved that the stock react to private equity placement positively and response to the open offer negatively. In addition, the new investors who purchased the new shares of issuing firms in private equity placement are proved play an important role in monitoring the management of companies. In addition, certification effects of underwriter in open offer are not observed based on the results of this thesis, even though they are believed could mitigate the negative announcement effect of open offer by certifying firm value of issuing firms. However, the stock prices of companies whose new shares are underwritten by investment bank are indicated perform better than those companies underwritten by the largest shareholder of issuing firm.